AKTIVASI TEKNOLOGI DIGITAL KBBI VI DALAM MENGANALISIS DIKSI, RAGAM BAHASA DAN MAKNA LAGU ASMALIBRASI - Rina Hayati Maulidiah; Eva Fitrianti (Smart Education, 2025)
Abstract: This study aims to describe the activation of digital technology from the Big Indonesian Dictionary (KBBI) VI edition in analyzing the diction in the song Asmalibrasi. The use of this digital dictionary is considered important as a source of information in searching for word meanings according to the Indonesian dictionary online. Then the researcher is also interested in knowing the meaning of the song, as well as what language variations are found in the song. The researcher's interest in this song began with the song's title which is considered unique, with its unusual choice of words but has an element of beauty. This makes the researcher interested in finding out what the words of the song title mean and several other word choices so that they can find the intended meaning. Based on the analysis, it is known that the meaning of the song is telling about a relationship that has found a point of similarity